Retention of radiotransmitters tail‐mounted on 6 bird species. (12th January 2018) - Stanton, Richard A.; Burke, Alicia D.; Carrlson, Kaylan M.; Kesler, Dylan C.; Faaborg, John; Thompson, Frank R.
ABSTRACT: Radiotransmitters can be tail‐mounted using cyanoacrylate glue and an accelerant rather than using a harness. Tail‐mounted transmitters are dropped or shed when the rectrices molt, which may reduce transmitter effects while providing retention times sufficient for most research objectives. However, retention times of tail‐mounted transmitters for birds are insufficiently described, and bias from not following all birds until transmitters are shed has been ignored. We studied transmitter retention of 106 birds of 6 species in the United States of America, 2010–2013, using direct observations and survival modeling based on radiotelemetry tracking. Cox proportional hazard survival models predicted median transmitter retention times from 4 to 53 days, depending on species. Our results suggest that researchers should anticipate premature (i.e., <30 days) tag loss rates from 15% to 38% for adult birds, and adjust permit and funding applications accordingly. However, predicted premature tag loss approached 100% for independent juvenile birds, which frequently appeared to disperse long distances, leading to few or no failure events to inform models. Overall, our results provide guidance for the design of future telemetry studies while demonstrating that tail‐mounting transmitters can yield adequate data for a variety of research objectives. © 2018 The Wildlife Society. Abstract : Tail‐mounted radio transmitters are used to study birds, but retention times remain insufficiently described and bias from not following all birds until transmitters are shed has generally been ignored. We used Cox proportional hazard survival models to estimate transmitter retention times for 6 North American bird species, finding that tail‐mounted transmitters were generally retained long enough to be suitable for studies lasting ≤30 days.